2011
DOI: 10.1007/s12034-011-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and investigation of Al–4 wt % B4C nanocomposite powders using mechanical milling

Abstract: Boron carbide nanoparticles were produced using commercially available boron carbide powder (0•8 μm). Mechanical milling was used to synthesize Al nanostructured powder in a planetary ball-mill under argon atmosphere up to 20 h. The same process was applied for Al-4 wt % B 4 C nanocomposite powders to explore the role of nanosize reinforcements on mechanical milling stages. Scanning electron microscopy (SEM) analysis as well as apparent density measurements were used to optimize the milling time needed for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…The Al-B 4 C composites are used in bicycle frames, bullet proof vests, armor tanks, containment of nuclear waste, neutron absorbers in nuclear power plants, transportation applications, etc. owing to their high hardness, low density, and excellent thermal and chemical stability [ 9 , 10 ]. Recently, Al-B 4 C composites were prepared through different techniques: stir casting [ 11 ], squeeze casting [ 12 ], powder metallurgy method [ 13 ], spark plasma sintering [ 14 ], and microwave sintering [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Al-B 4 C composites are used in bicycle frames, bullet proof vests, armor tanks, containment of nuclear waste, neutron absorbers in nuclear power plants, transportation applications, etc. owing to their high hardness, low density, and excellent thermal and chemical stability [ 9 , 10 ]. Recently, Al-B 4 C composites were prepared through different techniques: stir casting [ 11 ], squeeze casting [ 12 ], powder metallurgy method [ 13 ], spark plasma sintering [ 14 ], and microwave sintering [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For FCC metals, it has been indicated that the intensity ratio of (111) to (200), I(111)/ I(200), can reflect the change in crystallographic orientation of particles in the ball milling process. While for BCC metals, I(110)/ I(200) is used (Razavi-Tousi and Szpunar 2015; Alizadeh et al 2011). As shown in Fig.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…This process is faster for the Al-GNSs composite due to the aforementioned localised stress induced by the addition of GNSs. This could be explained by considering the anisotropy in the elastic modulus of a single aluminium crystal (Alizadeh et al 2011). To be specific, the aluminium grains/particles tend to be deformed in the soft direction (111), which is perpendicular to the collision direction of milling balls.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…Despite the trend of the changes in the shape and size of the particles, the A change in crystallographic orientation of particles can also be used to monitor the milling progress. It has been proved that the ratio of intensity of (111) to (100) reflections for FCC metals [8,10,35,36], and the ratio of (110) to (200) reflections for BCC metals [11] can reveal changes in orientation and morphology of particles during milling. Fig.…”
Section: Imperfections and Orientation Changesmentioning
confidence: 99%
“…D. R. Amador et al ascribed the evolution of texture during ball milling of metallic powders to the presence of so called "soft" directions [11]. They explained the preferred orientation based on the difference in elastic modules of different directions of crystalline materials, the idea that was later echoed in other works [10,36]. The authors of the present work found this explanation unconvincing because plastic deformation of metals is based on the movement of dislocations rather than the effect of elastic modules.…”
Section: Imperfections and Orientation Changesmentioning
confidence: 99%